2022
DOI: 10.1021/acssuschemeng.2c01274
|View full text |Cite
|
Sign up to set email alerts
|

Using Undigested Biomass Solid Leftovers from the Saccharification Process to Integrate Lignosulfonate Production in a Sugarcane Bagasse Biorefinery

Abstract: Innovative schemes for lignocellulosic biomass refining could optimize the chemical use and biomass conversion efficiency, providing diversified biorefinery products. A new biorefinery scheme used mild alkaline-sulfite chemithermomechanical processing to pretreat sugarcane bagasse, producing highly digestible solids and diluted lignosulfonates in the black pretreatment liquor. Most of the glucan and xylan contained in the pretreated solids were converted into monosaccharides by saccharification with commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Previous work demonstrated that GAX extraction also benefits subsequent saccharification of remaining solids by commercial enzyme cocktails once the residual polysaccharides became more accessible to cellulolytic enzymes ( Sporck et al, 2017 ). After completing this biorefinery schedule, residual lignin from the final saccharification step can be converted into marketable lignosulfonates, as recently reported in Heinz et al (2022) .…”
Section: Discussionmentioning
confidence: 93%
“…Previous work demonstrated that GAX extraction also benefits subsequent saccharification of remaining solids by commercial enzyme cocktails once the residual polysaccharides became more accessible to cellulolytic enzymes ( Sporck et al, 2017 ). After completing this biorefinery schedule, residual lignin from the final saccharification step can be converted into marketable lignosulfonates, as recently reported in Heinz et al (2022) .…”
Section: Discussionmentioning
confidence: 93%
“…Lignosulfonates are highly dependent on NaOH (13% w/w) at 159 °C and 4% H 2 SO 4 at 121 °C for 1 h whenever the reslufonation reaction is enhanced. 68 The process of adding sulfuric acid to lignin, known as the sulfite procedure, can make it hydrophilic and improve its ability to allow water to pass through. Lignosulfonate, a type of lignin, has a higher molecular weight sulfonate group that ranges per unit of phenyl propane, between 0.4 and 0.7.…”
Section: Lignin Extraction Methodsmentioning
confidence: 99%
“…Because of the environment’s acidity, predominantly α-sulfonated β-O-4′alkyl-aryl ether bridge is broken via a quinone methide intermediate or through nucleophilic substitution. Lignosulfonates are highly dependent on NaOH (13% w/w) at 159 °C and 4% H 2 SO 4 at 121 °C for 1 h whenever the reslufonation reaction is enhanced . The process of adding sulfuric acid to lignin, known as the sulfite procedure, can make it hydrophilic and improve its ability to allow water to pass through.…”
Section: Lignin Extraction Methodsmentioning
confidence: 99%
“…Still on the valorization of black liquor and the residual solid fraction from enzymatic hydrolysis, Heinz et al [144] conducted a study on utilizing these two streams for lignosulfonate production from SCB. The combined stream obtained from the union of these side-streams was re-sulfonated to enhance the concentration of lignosulfonate in the liquid stream.…”
Section: Future Perspectives On Product Diversification For 2g Ethano...mentioning
confidence: 99%